Application of a new sternoclavicular hook plate in bipolar clavicle injuries - Zhang, Han; Zhu, Zhong; Lin, Lie; Cai, Guoping (Frontiers in Surgery, 2023)
Objective To evaluate the safety and effectiveness of using a new sternoclavicular hook plate combined with a shoulder locking hook plate for the treatment of bipolar clavicle injuries. Methods Retrospective analysis of 7 patients with bipolar clavicle injury, all-male, with a mean age of 51.1 years, who underwent a new sternoclavicular hook plate combined with a shoulder clavicular hook plate implantation. Results All 7 patients were fixed with a sternoclavicular hook plate combined with a repositioned shoulder locking hook plate and received 13-24 months of follow-up. There were no postoperative complications, no wound infections, and no plate or screw fractures. The mean ASES score was 94.3±2.8. Conclusion The safety and effectiveness of a new sternoclavicular hook plate combined with a shoulder locking hook plate in the treatment of bipolar clavicle injuries.